2018
DOI: 10.1089/sur.2017.288
|View full text |Cite
|
Sign up to set email alerts
|

Status and Challenges of Predicting and Diagnosing Sepsis in Burn Patients

Abstract: Burns are a common form of trauma that account for more than 300,000 deaths each year worldwide. Survival rates have improved over the past decades because of improvements in nutritional and fluid support, burn wound care, and infection control practices. Death, however, remains unacceptably high. The primary cause of death has changed over the last decades from anoxic causes to now predominantly infections and sepsis. Sepsis and septic complications are not only major contributors to poor outcomes, but they f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 67 publications
1
12
0
1
Order By: Relevance
“…(74/1624), 9.09% (166/1827), respectively. Burn patients have skin barrier damage, long hospitalization period, ventilator and other interventional operations, which can easily lead to burn wound, bloodstream, respiratory tract and urinary tract infection [2,3,6,7,21,22]. From the sites of infection, K.pneumoniae mainly were isolated from wound secretion, bloodstream and sputum during the past 10 years, and the proportion of isolation almost being no change.…”
Section: Discussionmentioning
confidence: 99%
“…(74/1624), 9.09% (166/1827), respectively. Burn patients have skin barrier damage, long hospitalization period, ventilator and other interventional operations, which can easily lead to burn wound, bloodstream, respiratory tract and urinary tract infection [2,3,6,7,21,22]. From the sites of infection, K.pneumoniae mainly were isolated from wound secretion, bloodstream and sputum during the past 10 years, and the proportion of isolation almost being no change.…”
Section: Discussionmentioning
confidence: 99%
“…Results on the utility of PCT levels to early detect sepsis in burned patients are controversial, probably the use of different combinations of different biomarkers could overcome their individual limitations (137,138).…”
Section: Pct In Infectious Complications Of Burnsmentioning
confidence: 99%
“…More recently, the publication by Stanojcic and colleagues as well as Yan and colleagues demonstrated that the Sepsis-3 had superior sensitivity in predicting sepsis in comparison to Mann-Salinas and ABA criteria for sepsis; however, none of the aforementioned had the accuracy to be a stand-alone diagnostic tool within the burn population [ 53 , 54 ].…”
Section: Guidelines For Sepsis Resuscitationmentioning
confidence: 99%